ACOUSTIC DETECTION AND CHARACTERIZATION OF MARINE SEDIMENT WITH SHALLOW SEISMIC TECHNOLOGY IN RAMBAT WATERS, BANGKA BELITUNG - Haqqu Ramdhani; Henry M. Manik; Susilohadi Susilohadi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
High resolution of marine seismic reflection seismic were used to detect the layers of seafloor sediment and to interpret the seismic data geologically. The objectives of this study weres to detect and to characterize the seafloor sediment in the Rambat area, West Bangka, Bangka Belitung. Acquisition data was held on 10-24 August 2012 located between 105.1°00'00